Moral Teachings in the Holy Books, the Bible and the Quran, About the Relationship of the Human to Nature: A Macedonian Research Project - Cacanoska, R., Lazarevski, P., Matlievska, M., Dauti, H., Zabijakin Chatleska, V., Gjorgjevski, Gj. and Zvrleska, D. (George Fox University, 2019)
The subject matter of this manuscript is the separation and actualization of the thematic areas of the holy books, the Bible and the Quran, in which the human-nature relationship is elaborated, indicated or specified. The emphasis is on the moral teachings contained in the holy books, the Bible and the Quran, which, refer to the human–nature relationship and their influence on the development of ecological awareness in that context, are supported by or grounded in the holy books. The empirical research point to the conclusion is that religion is an important source or basis of morality, and it determines the attitude of humans to nature. In that sense, religious collectivities/communities can and should be much more involved in issues related to environmental protection.
Keywords: Bible; Quran; moral teachings; ecological crisis; public religion